PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - B51109077, Nur Khodijah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
This study that entitled Analysis of Factors that Affecting Dividend Per Share in Manufacturing Companies Listed in Indonesia Stock Exchange (IDX). This study intended to know how big the factors about current ratio, debt to equity ratio, earning per share, affected to dividend per share, also to know the effect simultaneously or partially against it. Analysis with multiple regression against 30 companies which taken with purposing sampling in Indonesian Stock Exchange through yahoo finance. Observing periode is about 2009 to 2012. Analysis regression result did when the model was freed from classical assumption symptoms were normality, multicollinearity, autocorrelation, and heteroscedasticity. The result of study partially and simultaneously found that variable in model study which are current ratio, debt to equity ratio, earning per share, affected significant against dividend per share. Coefficient of determination value (R2) about 0,671 or 67,1%. This means 67,1% Dividend Per Share that can be explained by various of three independend variable like Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), while the rest of it about 100% - 67,1% = 32,9% explained by the other cause outside the models or variables. Keywords : Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), Dividend Per Shared (DPS)